Do you know? Factors Affecting Market Cleanliness that Should Not Be Ignored - Finta Amalinda; Fardiansyah Dunggio; Nur Rismawati (Yayasan Sinergi Kawula Muda, 2024)
The Bunta Traditional Market still looks dirty due to the rubbish left by traders strewn all over the place. Storage facilities, collection methods, temporary waste storage areas, and transportation methods do not meet health requirements, and waste processing still needs to be created. This research aimed to determine the factors related to the cleanliness of the Bunta People's Market, Banggai Regency. The research method used is quantitative, using an analytical survey design with a cross-sectional approach. Based on the research results, which were proven in statistical tests with a value of ρ = 0.645 (ρ value ≤ 0.05), there is no relationship between market cleanliness and SPAL conditions at the Bunta People's Market, Banggai Regency. The value is 0.008 (ρ value ≤ 0.05); namely, there is a relationship between market cleanliness and the condition of the trash bins at the Bunta People's Market, Banggai Regency. The value of ρ = 0.00 (ρ value ≤ 0.05) is that there is a relationship between market cleanliness and the behaviours of traders, visitors, and the public at the Bunta People's Market, Banggai Regency. It is expected that traders, visitors, the public, and market managers will always maintain the cleanliness of the market environment and that market managers will make every effort to provide rubbish bins so that the market remains clean.